Human and social capital as drivers of entrepreneurship - Carolina Madriz; Juan Carlos Leiva; Ralph Henn (Small Business International Review (SBIR), 2018)
The objective of this study is to determine whether human and social capital are drivers of entrepreneurship. The methodology involves the estimation of descriptive and inferential statistical techniques such as logistic regressions and correlations of variables. It is focused on information from the Global Entrepreneurship Monitor database for 2012 from Germany and Costa Rica. The results demonstrate that human and social capital, factors related to knowledge, have a positive statistical relationship with the propensity to become an entrepreneur. Little difference exists among knowledge-related factors across countries. They are mainly related to the cultural contexts, which affect the propensity to become an entrepreneur.
Keywords: J14; L26; Z13; 650; knowledge; self-efficacy; entrepreneurship; human capital; social capital; conocimiento; auto eficacia; emprendimiento; capital humano; capital social